The Effect Of Customer Experience And Price On Repurchase Intention (A Study on Manor Studio's Coffee Shop Customers) - Iqbal, Said; Safrin, Feby Aulia (Cattleya Darmaya Fortuna, 2023)
Customer experience is an effort to create customer satisfaction through experience, based on the product or service offered. Customer experience rating depends on the comparison between coffee shop management performance and consumers expectations. In an effort to build a positive customer experience, precise pricing is a need. Therefore, the coffee shop needs to analyze and determine who is the target market in order to facilitate the implementation of the customer experience and pricing. This study aims to analyze the influence of customer experience and price on repurchase intention at Manor Studio coffee shop. The form of research used in this study is quantitative research with a descriptive approach. The data analysis methods used are validity test, reliability test, classical assumption test, multiple linear regression analysis, and hypothesis test. The results of this study indicate that customer experience and price have a significant effect either partially or simultaneously on repurchase intention in Manor Studio. The coefficient of determination test shows a close relationship between customer experience and price on repurchase intention with an R value of 0.873. Through the adjusted R square value, it is also known that customer experience and price variables contribute 75.7% to the variable of repurchase intention.